IMPLEMENTASI KOMUNITAS BELAJAR GURU DALAM MENINGKATKAN KOMPETENSI GURU DI SEKOLAH DASAR - Jamilah, Evie; R Supyan sauri; Aas Purnamasari; Iman Ramadan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the implementation of teacher learning communities in enhancing teacher competence at SDN Paripurna, Jatinangor District, Sumedang Regency. The research aims to describe and analyze the stages of planning, implementation, evaluation, and follow-up while identifying key challenges and solutions. Using a qualitative case study design, data were collected through interviews, observations, and document analysis involving teachers and  principals.The findings reveal that teacher learning communities play a significant role in improving pedagogical, professional, social, and personal competencies through collaboration, reflection, and shared practices. The success of the program is supported by systematic planning, strong leadership engagement, and a culture of continuous reflection. The main challenge lies in time management and varying levels of understanding among teachers, which at times affect participation and focus. To address these issues, strategies such as better time management, innovative implementation methods, and stronger leadership support have been applied. Overall, teacher learning communities foster a culture of lifelong learning and contribute meaningfully to improving the quality of elementary education.